Black earth, white bread a technopolitical history of Russian agriculture and food - Wengle, Susanne 1977- (University of Wisconsin Press, 2022)
Intro -- Contents -- List of Illustrations -- Acknowledgments -- Note on Transliteration, Translation, and Place-Names -- Introduction: Setting the Table -- 1. Governance -- or, How to Solve the Grain Problem -- 2. Production -- 3. Consumption -- or, Perestroika of the Quotidian -- 4. Nature -- Conclusion: Vulnerabilities -- Notes -- Bibliography -- Index.